Optimisation of TNI Personnel Postings Using an Android-Based AHP System - Syahfrizal Fakhri Irawan; ginanjar setyo permadi; Tanhella Zein Vitadiar (LPPM Universitas Bina Sarana Informatika, 2026)
Efficiency and objectivity in the placement of Indonesian National Armed Forces (TNI) personnel are crucial aspects of military human resource management. This study aims to develop an Android-based personnel placement recommendation system using the Analytic Hierarchy Process (AHP) method to support faster, more accurate, and consistent decision-making. The study population comprised 300 active TNI personnel, with a purposive sample of 120 personnel possessing complete data on rank, length of service, education, competency, and disciplinary records. Data were collected from internal documents, personnel records, performance reports, and information from the TNI Air Force Planning and Budget Staff. The results indicate that rank and length of service are the dominant criteria, while education, competency, and disciplinary records provide additional contribution. The system generates objective, consistent, and user-friendly recommendations, validated through functionality and user acceptance testing. The findings demonstrate that implementing AHP in an Android-based recommendation system enhances efficiency, transparency, and objectivity in personnel placement and has potential for adoption in other TNI units or similar military organizations